The precarious role of emerging powers in a transforming international order: the Brazilian and Turkish initiative for a nuclear deal with Iran - González Levaggi, Ariel (2019)
Fil: González Levaggi, Ariel. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Departamento de Ciencias Políticas y Relaciones Internacionales; Argentina